LINC00973 is involved in cancer immune suppression through positive regulation of Siglec‐15 in clear‐cell renal cell carcinoma. Issue 10 (31st August 2020) - Liu, Yanbin; Li, Xingzhi; Zhang, Changming; Zhang, Hui; Huang, Yali
Abstract: The pioneering work from Lieping Chen's laboratory identified Siglec‐15 as a novel tumor immune suppressor, while the regulatory mechanisms underlying the broad upregulation of Siglec‐15 in human cancers remain obscure. Here we found that long non–coding RNA (lncRNA) LINC00973 was higher in Siglec‐15‐positive clear‐cell renal cell carcinoma (ccRCC), and LINC00973 positively regulated Siglec‐15 expression at transcriptional level. This effect was evidently dependent on miR‐7109‐3p (designated as miR‐7109 hereafter), and we provided evidence that Siglec‐15 is a direct target of miR‐7109. Through sponging miR‐7109, LINC00973 functioned as competing endogenous RNA (ceRNA) to control cell surface abundance of Siglec‐15, and, consequently, was involved in cancer immune suppression. We further demonstrated that LINC00973 and miR‐7109 expression in ccRCC antagonistically influenced immune activation of co–cultured Jurkat cells. Our study highlighted the importance of LINC00973‐miR‐7109‐Siglec‐15 in immune evasion in ccRCC, which offers significant opportunity for both therapeutic intervention and diagnostic/prognostic exploitations. Abstract : Through sponging miR‐7109, LINC00973 functioned as competing endogenous RNA (ceRNA) to control cell surface abundance of Siglec‐15, and, consequently, was involved in cancer immune suppression. LINC00973 and miR‐7109 expression in ccRCC antagonistically influenced immune activation of co–cultured Jurkat cells.